Prevention of Divorce through the Marriage Certification Program in Cilacap Regency, Central Java: The Lens of al-Ghazālī’s Maṣlaḥah - Santoso, Selamet; Arifin, Tajul; 'Ain, I. Nurol; Nurrohman, Nurrohman (Sawwa: Jurnal Studi Gender, 2023)
Cilacap Regency, Central Java, has experienced a significant increase in divorce cases and is ranked the highest in the region. In response to this trend, the Ministry of Religious Affairs in Cilacap launched a marriage certification program to counteract the spike in divorce rates. Using a qualitative research design, this study used primary data from interviews and secondary data from an information review involving KUA officers and certification counselors in Cilacap Regency. Data validation used the triangulation method, and analysis interpreted the information thematically through al-Ghazālī maṣlaḥah theory. This study aims to examine the application of al-Ghazālī maṣlaḥah theory in the implementation of the marriage certification program in Cilacap Regency. The findings of this study highlight the program’s alignment with al-Ghazālī maṣlaḥah theory, categorizing it as maṣlaḥah ḍarūriyyah (primary), which requires an immediate implementation to uphold the objectives of Sharia: safeguarding religion, mind, soul, property, and offspring.